(untitled) (Research, Society and Development, 2021)
This work is linked to the line of research Teaching and Learning in Science and Mathematics of the Graduate Program in Teaching Science and Mathematics - Professional Master’s Degree, from the Franciscan University. It aims to develop and apply a didactic resource, in the form of pedagogical games, directed to the teaching of Science and Mathematics in Inclusive Education, contemplating the general competencies of the Common National Curricular Base for Elementary Education - Final Years. This study had as reference the Common National Curricular Base (BRASIL, 2017), focusing on the interdisciplinarity of Inclusive Education. The target audience was students with Disabilities and / or with Specific Learning Difficulties, enrolled at the Alfredo Schlesner Municipal Elementary School – Specialized Educational Center, in the Municipality of Paraíso do Sul, in Rio Grande do Sul. Qualitative aspects and pedagogical games were produced as a didactic resource. The games produced were: Division Trail, Roulette of Numbers, Tangram of Birds and Battle of Words. A didactic sequence for the application of the games was used as a teaching strategy.